Drugs as a provoking factor of connective tissue diseases - Błaszczyk, Maria (Dermatology Review/Przegląd Dermatologiczny, 2010)
Drugs are regarded as a one of provoking factors of connective tissue diseases (CTD), mainly lupus erythematosus (LE) and less frequently dermatomyositis (DM) and scleroderma. The pathomechanisms of drug-induced CTD are still unclear. Drug-induced lupus (DILE) is defined as lupus-like syndrome and can be divided into systemic (SLE), subacute cutaneous (SCLE) and chronic cutaneous form. Some drugs provoke clinical symptoms and immunological abnormalities (antinuclear antibodies – ANA) characteristic of LE, while others induce ANA only. In the majority of patients symptoms of DILE as well as ANA clear after withdrawal of the offending drug; however, in some cases they persist and the disease runs a course similar to idiopathic LE. CTD-provoking drugs come from various therapeutic groups: antiarrhythmics, antihypertensives, anticonvulsants, diuretics, antibiotics and other medications including statins and TNF-a inhibitors. Statins, one of the most widely prescribed drugs in adults, can provoke not only DILE, but also other autoimmune diseases, e.g. dermatomyositis. Skin lesions characteristic of DM with or without muscle involvement are also observed in patients treated for a long period with hydroxyurea and other cytotoxic drugs. Cases of drug-induced skin indurations resembling localized or systemic scleroderma, in some cases with Raynaud’s phenomenon, are observed mainly after anticancer medications: bleomycin, taxanes, melphalan and others. In the last years cases of DILE and DM induced by TNF-a inhibitors in patients with rheumatoid arthritis have been published. To sum up, it is necessary to remember that various medications may not only induce the disease but also exacerbate or reveal latent CTD or provoke allergic reactions which can influence the course of connective tissue disease.